Multiple granuloma annulare in a 2-year-old child - Karjigi Siddalingappa; Sambasiviah Chidambara Murthy; Kallappa Herakal; Marganahalli Ramachandra Kusuma (Wolters Kluwer Medknow Publications, 2015)
Granuloma annulare is a benign, self-limiting, inflammatory and granulomatous disease of unknown etiology occurring in both adults and children. An 18-month-old male child had multiple progressive annular plaques over the lower extremities. Clinical and histopathological features were consistent with granuloma annulare. Localized granuloma annulare is the most common form in children.We report a young child with multiple, progressive granuloma annulare over the lower extremities.